2018
DOI: 10.1177/0194599818758995
|View full text |Cite
|
Sign up to set email alerts
|

Tracheotomy for Difficult Airway Foreign Bodies in Children

Abstract: No sponsorships or competing interests have been disclosed for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The result of this change is the rapid development of neurosurgery, and neurological severe disease has played a very important role in the development of neurosurgery. Neurocritically ill patients often use artificial airways because of their illness [ 2 ]. Generally speaking, patients who may use a ventilator for a long time will undergo tracheotomy.…”
Section: Introductionmentioning
confidence: 99%
“…The result of this change is the rapid development of neurosurgery, and neurological severe disease has played a very important role in the development of neurosurgery. Neurocritically ill patients often use artificial airways because of their illness [ 2 ]. Generally speaking, patients who may use a ventilator for a long time will undergo tracheotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Jiaqiang S et al reported that pen cap inhalation was 2.65% of all cases, most frequently found in patients aged 6 to 14 years, and 76.4% of them were in the right main stem bronchus ( 13 ). Our result showed that most (86.7%) cases of pen aspiration occur in school age children (over 6 years old) because students are accustomed to placing pens in their mouth and then inhaling the objects when talking or laughing ( 14 ). 85.7% in cases of light-emitting diodes and 83.3% in cases of plastic parts of toys were accidents in preschool children due to their playful activity and propensity to bite toys.…”
Section: Discussionmentioning
confidence: 76%
“…Endoscopy showed that the vocal cords were in an adducted position in a 1-year-old child who spontaneously breathed under inhalation anesthesia ( 25 ). The object lodged below the vocal cords is dangerous and could cause dyspnea at any time, such as a board game piece or a pen cap ( 14 ). When an unusually shaped foreign body directly passes through the vocal folds and completely obstructs the respiratory tract, particularly in children, the patients undergo choking episodes and lie between life and death ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although flexible bronchoscopy can be considered as a valid option for FB retrieval, rigid bronchoscopy should be always available in the operative room and the surgical team should be qualified and ready to switch to any surgical option such as tracheostomy and/or bronchotomy [24].…”
Section: Discussionmentioning
confidence: 99%